Analysis of discharge energy on surge arrester configurations in 132 kV double circuit transmission lines. (June 2019) - Nor Hassan, Nor Hidayah; Abu Bakar, Ab Halim; Illias, Hazlee Azil; Abd Halim, Syahirah; Mokhlis, Hazlie; Terzija, Vladimir
Highlights: Several surge arrester configurations on a 132 kV double circuit transmission line were modelled. The energy discharged by lightning strokes during back flashover phenomena was investigated. The most effective protection design were determined based on the actual tripping pattern. Double circuit line tripping can be completely eliminated by installing arresters at each phase. The chosen arrester configuration provides sufficient protection to transmission lines. Abstract: Surge arrester has been proven to be the most effective application to provide optimum lightning protection for the transmission line. Thus, many works on optimizing lightning protection for transmission line have been conducted since the past. However, works on minimizing double circuit outages and surge arrester physical properties during transient overvoltages are less likely to be found. Therefore, in this work, several surge arrester configurations installed on a 132 kV double circuit transmission line were modelled using EMTP-RV to investigate their capability to withstand current and energy discharged by lightning strokes during back flashover phenomena. These configurations were then compared to determine the most effective protection design based on the actual tripping pattern recorded by the lightning detection system (LDS) in Malaysia. The selection was made by considering arresters' discharge energy due to variation in tower footing resistance, current magnitude, power frequency voltage, lightning tail time and front time, number of towers and span length. It was found that double circuit transmission line tripping can be completely eliminated by installing surge arresters at each phase conductor of one circuit. The selected arresters configuration provides sufficient lightning protection to the transmission line and complies with the discharge energy capability requirement specified by the utility company in Malaysia, of 5.1 kJ/kV for maximum continuous operating voltage (MCOV).